The University Idea and Possibilities for Its Realization [In Bulgarian] - B.V. Toshev (University of Sofia, 2011)
The mass higher education and the mcdonaldization of higher education are social phenomena which shape the contemporary higher education in the world. The number of the students/lecturers increase, the number of the institutions of higher education increase as well. At these conditions, the very university idea, pronounced short with the sentence "education and research belong together", appears to be under threat. What is the idea of a university, what are the axioms of higher education, what is higher education for, how many are the educational tracks where the higher schools could be situated in their own interest - these are the questions which are discussed in details in the present paper.